Osteoma de meato acústico externo: relato de nove casos e revisão de literatura - Testa, Jose Ricardo Gurgel [UNIFESP] (2003)
The osteoma of external acoustic meatus corresponds to an abnormal and benign bony growth, that is developed under the skin of the auditory canal and that can cause total or partial obstruction of the external acoustic meatus. STUDY DESIGN: Serie study. MATERIAL AND METHOD: We reported in this study nine cases of osteoma of external acoustic meatus. The patients' ages varied between 23 and 70 years old, being the average age 40,6 years. These patients were 5 of the feminine sex and 4 were of the masculine sex. RESULTS: The more common symptoms were hipoacusia, caused by the partial or total obstruction of the canal, appealing external otitis and also the accumulation of cerumen deep in the external auditory canal with difficult removal. CONCLUSION: We recommended in the presented cases surgical treatment, which had good evolution, with no recidivism.